Influence of Micron Roughness on Droplet Adhesion and Detachment Behavior with Coal Surfaces - Siheng Hou; Peng Xiong; Xianshu Dong; Hengfei Chen; Shuhuan Li; Yujin Sun (Separations)
Surface roughness directly affects the interaction between mineral surfaces and water, as well as the adhesion of particles to bubbles during mineral flotation processes. Currently, there is a significant amount of research on the relationship between mineral surface roughness and wettability, yet the conclusions drawn are not consistent. To investigate the impact of roughness on the adhesion and detachment behavior between droplets and coal surfaces, this study prepared a series of coal samples with varying roughness using sandpaper of different grit sizes. A highly sensitive adhesion force measuring instrument was employed to study the continuous attachment and detachment processes between droplets and coal surfaces of different roughness levels. Contact angle results indicated that as the roughness of the coal sample surface increased, the contact angle gradually decreased, suggesting an increase in the hydrophilicity of the coal surface. This study proposed a concavo-convex roughness model for predicting the contact angle on coal surfaces, which was validated for feasibility and accuracy through experimental data. The adhesion force between droplets and coal surfaces increased with roughness. As the roughness increased from 0.30 μm to 2.39 μm, the spreading force of the droplet increased from 159.00 μN to 209.60 μN, the maximum adhesion force increased from 406.76 μN to 441.08 µN, and the detachment force increased from 95.37 μN to 102.39 μN. A smaller contact angle between the droplet and the coal surface corresponded to a larger contact diameter and greater interaction force. The forces measured by the adhesion force measurement device showed good consistency with theoretical calculations. This study provides theoretical support for understanding the interaction processes between droplets and rough solid surfaces.